Do Employers Prefer Workers Who Attend For‐Profit Colleges? Evidence from a Field Experiment. (6th August 2015) - Darolia, Rajeev; Koedel, Cory; Martorell, Paco; Wilson, Katie; Perez‐Arce, Francisco
Abstract: This paper reports results from a resume‐based field experiment designed to examine employer preferences for job applicants who attended for‐profit colleges. For‐profit colleges have seen sharp increases in enrollment in recent years despite alternatives, such as public community colleges, being much cheaper. We sent almost 9, 000 fictitious resumes of young job applicants who recently completed their schooling to online job postings in six occupational categories and tracked employer callback rates. We find no evidence that employers prefer applicants with resumes listing a for‐profit college relative to those whose resumes list either a community college or no college at all.